Resource accumulation through economic ties: Evidence from venture capital - Hochberg, Yael V.; Lindsey, Laura A.; Westerfield, Mark M. (Journal of Financial Economics, 2015)
Ties between similar partners in economic and financial networks are often attributed to concerns about agency costs. In this paper, we distinguish the underlying motives for tie formation between sets of potential partners in the network, thus informing the relative importance of agency cost and resource accumulation in tie formation across firms. We develop a robust and generalizable methodology that allows for the inference of similarity and/or cumulative advantage motives in the potential presence of resource trading. We estimate the model using venture capital (VC) co-investment networks, employing factor analysis to characterize orthogonal, interpretable resources for VC firms. In the VC setting, value-added resources other than capital appear to be exchanged for capital, but not for one another. We find little evidence for similarity motives as the primary driver of matching, suggesting that concerns over agency conflicts in partnering are dominated by the desire to accumulate higher levels of certain resources.